Arbeitsmedizin und Facharztausbildung bei Medizinstudierenden - Hollederer, A.; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2018)
Aims: The occupational medicine’s significance increases clearly due to labour market developments in Germany. Information about the medical students’ specialist fields preferences and their influencing factors are essential for recruiting in occupational medicine. Method: In October 2016, 177 out of 208 participating medical students of the university Erlangen-Nuremberg were randomised assigned within the scope of mandatory internships in health services research. At the beginning, every one of the 177 participated voluntarily in an anonymous questionnaire (100% response rate). Results: 93% of the medical students attended the ninth or tenth semester, 58.2% were women. Training as specialists in internal medicine is chosen most often by the students followed by general medicine. 0.6% of the students would have chosen occupational medicine qualification; for 2.8% of the students, it would be worth considering in general. The non-professional factors variety in the job, a work-life-balance and income possibilities were of high importance. For students preferring training as specialists in occupational medicine, team-orientation with other health professionals and between specialist disciplines is especially important. As main reasons against a further training in occupational medicine it was stated the preference of other specialist fields, range of medical methods, a lack of variety in the job and a low level of information. Conclusions: The survey reveals reasons for the choice of occupational medicine qualification and “soft factors” like work-life-balance and team-orientation. It States needs for information about the methods and practice of occupational medicine. A stronger integration of occupational medicine into university education is recommended.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Medical students; Occupational health care; Occupational medicine; Occupational medicine qualification